SOME HUMAN AND TECHNICAL ASPECTS OF ONLINE CONTENT REGULATION - Gergely Gosztonyi (Institute for Research and European Studies, 2021)
The amount of newly uploaded content on the internet is growing daily: 60 seconds on the web in 2021 consist of more than 500 hours of content uploaded on YouTube, 695,000 stories shared on Instagram, and nearly 70 million messages sent via WhatsApp and Facebook Messenger. The vast majority of them is legal content, but a slice is illegal or harmful. The article analyses the situation and the problems of both human and AI moderation, then it gives an answer how to handle the content on the internet with a shared usage of human and AI moderation as they could perfectly complement each other in a long term.